Enhance Effectiveness Knowledge and Attitudes of Pregnant Women in Royal Prima Medan Hospital Based on Comparison Providing Verbal Information and Information through Presentation Media Video - Masyitah Masyitah; Ermi Girsang; Sri Lestari Ramadhani; Ali Napiah Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Early initiation of breastfeeding (IMD) is one way that can be done to reduce the risk of post partum bleeding in the mother and reduce infection after delivery. The purpose of this study was to determine the comparison of the effectiveness of providing verbal information and video presentation on the knowledge and attitude of pregnant women about early breastfeeding initiation based on age, education level, knowledge, attitude, at Royal Prima Medan General Hospital. Type of research used is the Quasi Experiment, Pretest and Post Test Controlled Trial. The sampling technique used total sampling with a sample size of 50 people. The conclusion from the results of the analysis using Wilcoxon, there is an effect of giving verbal and video information on the level of knowledge and attitudes of mothers about IMD with a p value of 0.00 <α 0.05. Based on the results of the regression test, there was no difference in the effectiveness of verbal information and presentation using video on the level of knowledge and attitudes of mothers about IMD with a significance value = 0.21 and p (0.21).